The greener shore : a novel of the druids of Hibernia - Llywelyn, Morgan (Ballantine, 2006)
As druids in Celtic Gaul, they had been the harmonious soul of their tribe. But when Julius Caesar and his army invaded and conquered their homeland, the great druid Ainvar and his clan fled for their lives, taking with them the ancient knowledge. Guided by a strange destiny, they found themselves drawn to a green island at the very rim of the world: Hibernia, home of the Gael.